2003
DOI: 10.1046/j.1524-4725.2003.29081.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonablative Radiofrequency for Active Acne Vulgaris: The use of Deep Dermal Heat in the Treatment of Moderate to Severe Active Acne Vulgaris (Thermotherapy): A Report of 22 Patients

Abstract: Nonablative radiofrequency appears to be a new safe and effective treatment alternative for moderate to severe acne vulgaris. Further research is in progress to evaluate this treatment modality in a larger number of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
93
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 33 publications
7
93
0
Order By: Relevance
“…Recently, several clinical studies have shown that heat may be beneficial for acne [67][68][69][70], which raises a possibility for our subjects to have benefited from the mild heat from the LED device. However, the devices used in those studies were specifically designed to deliver thermal energy to the dermis while used in contact with the skin surface, whereas the one used for our study was equipped with cooling fans to avoid heat generation, consisted of LEDs which have low heatemitting property, and was positioned 3-5 cm above from the skin surface during the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several clinical studies have shown that heat may be beneficial for acne [67][68][69][70], which raises a possibility for our subjects to have benefited from the mild heat from the LED device. However, the devices used in those studies were specifically designed to deliver thermal energy to the dermis while used in contact with the skin surface, whereas the one used for our study was equipped with cooling fans to avoid heat generation, consisted of LEDs which have low heatemitting property, and was positioned 3-5 cm above from the skin surface during the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Photodynamic therapy, using a variety of visible wavelengths and a number of photosensitizing dyes, has been used to treat acne [17,18]. In addition to visible wavelengths of light, radiofrequency has also been used to treat acne [22]. Recently, the most commonly used laser modalities for treating acne with electromagnetic radiation are the infrared lasers [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]6,7 Recently, nonablative lasers, light sources, and radiofrequency devices have been used to selectively deliver thermal energy to the upper dermis, inducing a controlled wound healing response in the papillary and upper reticular dermis without epidermal damage. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Histologic studies have confirmed production and deposition of new collagen after thermal damage induced by nonablative laser treatments. 10,14,18 Although previous studies have shown that nonablative laser treatments result in qualitative improvements in facial rhytids and scars, there has been an inherent difficulty in quantifying the effects of nonablative resurfacing.…”
mentioning
confidence: 99%